Implementation of Phase Locked Loop for FM Demodulator Circuit - Amit Deshmukh, Alpana; Gamad, Radheshyam; Kumar Mishra, Deepak (International Journal of Engineering and Technology, 2019)
This paper aims to implement the phase locked loop for the FM demodulator circuit in Intermediate frequency band. Implementation of the proposed design is done using Simulink; further simulation is presented using Matlab as well as a comparative analysis of VCO parameters using charge pump, linearized and baseband are discussed. Charge pump based PLL design achieved phase noise of -120 dBc/Hz at 10 MHz offset frequency. Paper also presented FM demodulated output for 5000 kHz sampling frequency and 2000 KHz carrier frequency at 50 Hz deviation frequency. Simulation results are reported in tabular and graphical form.Â Â